2023
DOI: 10.1021/cbmi.3c00023
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection and Staging of Lung Fibrosis Enabled by Collagen-Targeted MRI Protein Contrast Agent

Abstract: Chronic lung diseases, such as idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD), are major leading causes of death worldwide and are generally associated with poor prognoses. The heterogeneous distribution of collagen, mainly type I collagen associated with excessive collagen deposition, plays a pivotal role in the progressive remodeling of the lung parenchyma to chronic exertional dyspnea for both IPF and COPD. To address the pressing need for noninvasive early diagnosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…We have shown that ProCA32 agents exhibit both high r 1 (30 mM −1 s −1 at 1.4 T) and r 2 (42 mM −1 s −1 at 1.4 T) values that were 6-to 10-fold higher than clinically approved CAs at medical field strengths 1.5 T 50,52,59,116 (Fig. 2D).…”
Section: Rational Design and Optimization Of Protein Mri Contrast Age...mentioning
confidence: 87%
See 3 more Smart Citations
“…We have shown that ProCA32 agents exhibit both high r 1 (30 mM −1 s −1 at 1.4 T) and r 2 (42 mM −1 s −1 at 1.4 T) values that were 6-to 10-fold higher than clinically approved CAs at medical field strengths 1.5 T 50,52,59,116 (Fig. 2D).…”
Section: Rational Design and Optimization Of Protein Mri Contrast Age...mentioning
confidence: 87%
“…It is also important for the agent to reach the molecular biomarkers quickly to facilitate temporal imaging of dynamic molecular contrast enhancement that can provide important data related to disease vessel structure and subtle structural changes. 52,115,116 Fifth, rapid, quick, and complete clearance of the CA can reduce any potential toxicity. The agent should accumulate quickly in the organ/tissue of interest to reduce the waiting period for MRI scanning, followed by fast washout of unbound agent to improve targeted imaging.…”
Section: Criteria Of Ideal Mri Contrast Agents For Precision Mrimentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetic resonance imaging (MRI) has been widely used in clinical diagnostics . MRI is a noninvasive technique with the advantages of having extremely high spatial resolution and the absence of radiation exposure. This feature allows early detection of even tumors as small as a few hundred cells and hundreds of micrometers in size . However, MRI has low sensitivity and usually requires a contrast agent to increase its sensitivity.…”
Section: Construction Of Targeting Peptide-based Imaging Reagentsmentioning
confidence: 99%